Sustainable Development in Islamic Education: Embedding a Zero-Waste-Based Learning Program for Pre-Service Madrasah Teachers - Widayanti, Esti Yuli; Widyawati, Wiwin (Cendekia: Kependidikan dan Kemasyarakatan, 2024)
This study aims to formulate a learning program for the pre-service elementary madrasah teacher IAIN Ponorogo. This study is very important to be able to support sustainable development appropriate for environmental conservation. The program is supported with zero-waste aspect waste management materials which have been included in environment studying approach. Research and Development was used as a design of the study while this model belongs to eight instructional development phases, with or without modification in ADDIE Model. Observation was conducted to examine the implementation and process of the learning activities. Documentation was utilized to collect data from faculty and departmental administration, particularly regarding curriculum and its related components. Questionnaires were administered to students to gather feedback for product improvement during the trial phase. While to assess product effectiveness, data collection was carried out using test techniques. Results in a structured learning framework consisting of Course Learning Outcomes (CPMK), Semester Learning Plans (RPS), and Practical Guidelines. N-gain analysis demonstrates that the program is moderately effective in improving environmental knowledge and attitudes, but lowly effective in behavior changes as a recent activity. This implies that a systematic environmental learning approach is needed which needs to go beyond the boundaries of one course.